PELAKSANAAN PROGRAM PEMBERIAN KREDIT BPR (BANK PERKREDITAN RAKYAT) DANA AMANAH KABUPATEN PELALAWAN TAHUN 2012 - Anugrah, Harry; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
People assume that if the government really wants to help the middle and lower economic communities, the government should not have to pay interest loans to lower middle economic people and this will cause problems in achieving the goals of the program pemberan rural banks in one trust fund the customer is in arrears. The purpose of this study was to determine the factors causing non optimal implementation of economic empowerment programs through program lending trust fund BPR (Rural Bank) Pelalawan. In this study, the concept is derived from the theoretical evaluation of the implementation of Edward III declared that there are 4 (four) variables are crucial in the implementation of communication, resources, character or attitude and bureaucratic structures. The location of this study are in BPR (Rural Bank) Trust Fund Pelalawan. This study used qualitative research methods to the study of descriptive data. In collecting data the researcher used interview techniques and documentation. The results of this study it can be concluded that the implementation of the loan program BPR (Rural Bank) Pelalawan Trust Fund in 2012, can not be said to be effective, it can be proved from the 5 indicator variables are used as benchmarks in this study, almost all of the indicators are in the category less effective. For that expected in implementing these programs should be the implementing agency should consider that the effective lending strategies and efficient, BPR should conduct in-depth analysis of the internal condition of the RB.Keywords: Implementation, Program Lending, Trust Fund